Emile Littré and the death of Alexander the Great - Ernesto Damiani (Karanos)
The French philologist Émile Littré (1801-1881) is credited by several scholars as the first to propose that Alexander the Great died of malaria. This article demonstrates that this opinion of traditional origin is unsupported by Littré's scholarly production. He published only two full papers on the topic of Alexander's death, the first in 1844 and the latter in 1853. In both works he stated that Alexander died of a pseudo-continuous fever, that is, a long lasting fever characterized by initial phases of remission to become continuous at the end. This feverish pattern differed from that of intermittent fever of malarial type that Littré described in his medical Dictionary. The articles of 1865, 1872 and 1927 were reprints of the 1853 article. The 1927 version published in Æsculape was preceded by a preface in which the anonymous author arbitrarily introduced the new word “paludisme”, giving rise to the erroneous belief that has been handed down to date.